Experimental study of properties for sand brick with palm oil clinker as partial replacement for fine aggregate with ratio of 5%, 10% and 15% - Nur Syuhada, Hashim (2018)
In Malaysia, the palm oil industry produces millions of tonnes of industrial wastes and these wastes create huge storage and environmental problems. Thus, experimental work has been conducted in order to investigate the effectiveness of palm oil clinker (POC), a by-product from palm oil industry as partial replacement for fine aggregate in the properties of sand brick. The four types of samples with different percentages of palm oil clinker which are 0%, 5%, 10% and 15% had been prepared. In this study, there were two types of curing which are water curing and air curing and all specimens were cured for the 3, 7, 14 and 28 days. Different mechanical properties were studies including compressive strength, flexural strength, density and water absorption. The sand brick with POC replacement then were compared with normal sand brick. The result of this study indicates that replacement with 15% of palm oil clinker was the best compression strength, flexural strength, density and water absorption. The density and water absorption of the sand brick were increase slightly when the palm oil clinker used as partial replacement. On overall, the study indicates that POC can be used as partial replacement for fine aggregate in the production of sand brick and also can be used for non load bearing application. It also noted that the using of palm oil clinker in the production of sand brick can manage the waste and promote the environmental sustainability.